2021
DOI: 10.1186/s40560-021-00571-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of lactate clearance in patients with cardiogenic shock: results from the RESCUE registry

Abstract: Background Limited data are available on the clinical significance of lactate clearance (LC) in patients with cardiogenic shock (CS). This study investigated the prognostic role of LC in CS patients. Methods We analyzed data from 628 patients in the RESCUE registry, a multicenter, observational cohort enrolled between January 2014 and December 2018. Univariable logistic regression analysis was performed to determine the prognostic implications of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In this study, lactate clearance was higher with every observation interval, and its highest median was discovered at 24 h post-initial resuscitation. This is similar to the study conducted by Park et al, which stated that lactate clearance was highest in the 24-hour observation period [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, lactate clearance was higher with every observation interval, and its highest median was discovered at 24 h post-initial resuscitation. This is similar to the study conducted by Park et al, which stated that lactate clearance was highest in the 24-hour observation period [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Cardiac power did not correlate with the length of stay; however, higher lactate clearance during the first hour after initial resuscitation was correlated with a shorter length of stay in the hospital (r= -0.362, p = 0.017). Previously, a study by Park et al showed that patients with higher lactate clearance (≥64% in 24 h) had longer stay in the ICU (8.0 (4.0–16.5) days versus 6.0 (2.0–15.0) days, p = 0.002) and hospital (14.0 (8.0–28.0) days versus 11.0 (5.0–27.0) days, p = 0.001) [ 19 ]. However, it might be because of the higher in-hospital mortality rate in patients with lower lactate clearance (25.5% versus 42.7%, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Attana ´et al described the role of lower lactateclearance in higher mortality of patients with STEMI complicated by cardiogenic shock [16]. Recently, these initial results from 51 patients were confirmed by Park et al analyzing a large, multi-center registry with 628 cardiogenic shock patients [17]. Gjesdal et al found that blood lactate is a predictor of short-term mortality in PCI-treated patients with myocardial infarction complicated by mild to moderate heart failure even in the absence of cardiogenic shock [18].…”
Section: Context With Previous Reportsmentioning
confidence: 95%
“…Additionally, serial lactate measurements are a useful tool in order to estimate a patient’s response to therapy [ 51 ] and prognosis [ 21 ]. Recent studies underline the importance of lactate clearance ( LC ) as a prognostic marker, superior to baseline lactate, since higher LC has been significantly associated with better prognosis [ 52 , 53 ]. Lactate clearance is the reduction in lactate concentrations at two different timepoints and can be measured by calculating the percentage of the exact time difference (Δ t ) between lactate concentration on admission ( L 1) and lactate concentration after initial resuscitation ( L 2) [ 53 ].…”
Section: Initial Diagnostic Approachmentioning
confidence: 99%